Perceptions, barriers, and facilitators of maternal health service utilization in southern Ethiopia: A qualitative exploration of community members' and health care providers' views. - Amanuel Yoseph; Wondwosen Teklesilasie; Francisco Guillen-Grima; Ayalew Astatkie (PLoS ONE)
Introduction Maternal health service (MHS) use is a key strategy to reduce maternal mortality. However, evidence is scarce in designing efficient intervention strategies in Ethiopia. Thus, we aimed to explore community members and healthcare providers' perceptions of MHS and barriers and facilitators of MHS use in southern Ethiopia. Methods A phenomenological qualitative study was conducted in the month of November, 2022, in the northern zone of the Sidama region. There were sixteen in-depth interviews, nine focus group discussions, and 15 key informant interviews with 112 study participants. A maximum variance sampling method was used to select study participants. Data coding and analysis were done using MAXQDA 2020 software and presented in narratives. Results Communities have positive perceptions and good practices of skilled antenatal care (ANC) and health facility delivery (HFD) but lack awareness of postnatal care (PNC) services and schedules. Some have experienced negative interactions with health care providers, health facilities, and ambulance drivers. The main identified barriers to ANC use were lack of awareness of ANC benefits, distance from a health facility, costs associated with ANC use, long waiting time, lack of road access, and women being busy with different household chores. Distance from health facilities, costs associated with HFD use, unpredicted labor, lack of an ANC visit, lack of a birth preparedness plan, and non-dignified care were the main barriers to HFD. The major barriers to PNC use were home delivery, lack of awareness of PNC service and schedule, and socio-cultural beliefs. The main identified facilitators of MHS use were previous experience and fear of obstetric complications, health extension workers and women's development teams, and pregnant women's forums. Conclusions Rural women still encounter challenges when using MHS, even though communities have positive perceptions and good practices of skilled MHS. Bad experiences mothers faced in health facilities, challenges associated with the costs of MHS use, poor awareness of service, and unpredictable labor continued to be fundamental barriers to MHS use. Intervention approaches should consider inter-sectoral collaboration to address community and health facility barriers. The programs must emphasize the transportation arrangements during unpredictable labor and the needs of poor mothers and women with poor awareness of MHS at the community level.